2016
DOI: 10.1002/adfm.201505514
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Antiferromagnetic IrMn Electrode in Spin Thermoelectric Devices and Their Beneficial Hybrid for Thermopiles

Abstract: Seebeck coefficient S, high electrical conductivity σ, and low thermal conductivity κ, which are normally expressed by the thermoelectric figure of merit, ZT = σS 2 T/κ, where T is the absolute temperature. [1][2][3][4][5] To improve ZT, research on various materials has been performed, where κ is minimized by phonon engineering, [3] and the power factor (σS 2 ) is enhanced by modification of the band structure. [4] As an alternative and novel route to improve the thermoelectric efficiency, several interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…In addition, Figure c shows the dependence of the PTE voltage on laser power, which indicates a linear increase in the PTE voltage with laser power and, thereby, temperature gradient. These results confirm that the PTE voltage originates from the spin thermoelectricity as the spin thermoelectric voltage (Δ V ) is generated by the laser‐induced temperature gradient (∇ T ) via the spin Seebeck effect and anomalous Nernst effect as Δ V∼M × ∇ T , where M is the magnetization vector . In our sample geometry, under a vertical temperature gradient ∇ T z , the signal along the y ‐direction, V y , is maximized when M is aligned to the x ‐direction, as shown in Figure b.…”
Section: Resultssupporting
confidence: 79%
“…In addition, Figure c shows the dependence of the PTE voltage on laser power, which indicates a linear increase in the PTE voltage with laser power and, thereby, temperature gradient. These results confirm that the PTE voltage originates from the spin thermoelectricity as the spin thermoelectric voltage (Δ V ) is generated by the laser‐induced temperature gradient (∇ T ) via the spin Seebeck effect and anomalous Nernst effect as Δ V∼M × ∇ T , where M is the magnetization vector . In our sample geometry, under a vertical temperature gradient ∇ T z , the signal along the y ‐direction, V y , is maximized when M is aligned to the x ‐direction, as shown in Figure b.…”
Section: Resultssupporting
confidence: 79%
“…The exchange bias appears to be rather small (around 1 Oe), which is due to the thicknesses used in this work are smaller than the minimal thickness (≈10 nm) needed for exchange bias as used in ref. 34 .…”
Section: Resultsmentioning
confidence: 99%
“…In IrMn-CoFeB bilayers, it has been shown that the strength of the exchange-biasing depends on thickness. This has been put to use to make a thermopile 34 . It was also found that magnon transport around the phase transition of antiferromagnetic NiO layer 35 facilitates magnon-mediated spin torque switching.…”
mentioning
confidence: 99%
“…We then performed the heat transfer simulations to obtain the Δ T distributions in the FM layer by applying the material parameters as listed in Table 1 19 , 27 , 28 in the Fourier equation 21 . Figure 5(a) shows the calculated profiles of the Δ T s, m (mK) at the center of the laser spot along the (CoFeB) film normal based on simulated and measured parameters.…”
Section: Resultsmentioning
confidence: 99%